Penerapan Permainan Tradisional Bentengan Terhadap Agility Siswa Sekolah Dasar - Ilmiawan, Muhammad Taufiq; Muhammad , Heryanto Nur; Hidayat , Taufiq; Wibowo, Sapto (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Physical education for children is very important because it will result in the goal of improving children's physical skills and interests in the long term. Children's motor development is related to the development of their motor skills and abilities. All the movements and games that children do show the development of their motor skills. Agility is the ability to combine various movements and change direction quickly. Training agility requires proper training to be able to combine various movements and change direction quickly. One of them is Keboansikep 1 Gedangan State Elementary School in Sidoarjo Regency which has never held traditional fort game training. A quantitative descriptive study using the quasi-experimental method3 using a single-group pretest and posttest research design.In this study, purposive sampling technique was used to take a sample of 20 students. therapy for 16 meetings. Data collection was conducted through the Illinois skills test and skills measurement. The research results used the T test, or paired sample t test. The results of the study using the T test showed that the t value (53.56) was greater than the t table (0.05) (19) (2.093) and P (0.000) was smaller than α (0.05). Students at Keboansikep 1 Gedangan Public Elementary School, Sidoarjo Regency, demonstrate the differences between agility training and traditional fortification games. After treatment, there was a change. Students of Keboansikep 1 Gedangan State Elementary School, Sidoarjo Regency, showed a 9.7% increase in agility as a result of traditional fortification game training.